Comparative Study on Leadership Styles and Customer Behavior: Environmentalist and Non-Environmentalist Students, Barcelona, Spain - Aida MEHRAD; Hamza BOUTAMENT; Neema GEORGE RWERAMILA; Mohammad Hossein TAHRIRI ZANGENEH; Meriem BOUZEDIF; Rashi SHAH; Isaiah NKETIAH (Journal of Emerging Trends in Marketing and Management)
The study delves into the relationship between sustainability, consumer behavior, and leadership styles among students at C3S Business School in Barcelona. It focuses on the impact of ecological consciousness, which refers to environmental awareness and concern, on purchasing decisions and leadership practices. In the current context, with sustainability increasingly crucial in decision-making, individuals and organizations are reassessing their actions considering ecological concerns. The literature suggests a growing demand for sustainable products driven by heightened environmental awareness among consumers, especially millennials. Despite this trend, there is a noticeable gap between attitudes and behaviors, with many environmentally conscious individuals needing help translating their values into consumer choices. The research uses a qualitative approach, combining semi-structured interviews and online questionnaires. Semi-structured interviews allow in-depth exploration of students' environmental attitudes and behaviors, while online questionnaires provide a broader perspective. This approach was chosen to ensure a comprehensive understanding of how students identify with environmentalism and its impact on consumer behavior. The study categorizes participants into environmentalist and non-environmentalist groups, analyzing their motivations, purchasing behaviors, and the influence of leadership styles on their decisions. Key findings reveal that transformational leadership styles significantly enhance pro-environmental behaviors among students, aligning personal values with sustainable practices. These findings have practical implications for businesses and educational institutions, highlighting the role of leadership in promoting sustainable behaviors.